The first report of antibiotic resistance and virulence factor profiles in multidrug-resistant clinical isolates of from Pontianak, Indonesia - Mardhia Mardhia; Delima Fajar Liana; Mahyarudin Mahyarudin; Hariyanto Ih (Osong Public Health and Research Perspectives)
Objectives Klebsiella pneumoniae is known as one of the most common causes of hospital-acquired infections. Its prevalence poses substantial challenges to both hospital and public health systems, particularly due to the rise of multidrug‐resistant strains. Understanding the epidemiology and resistance properties of K. pneumoniae can inform antimicrobial stewardship and infection control programs. A cross-sectional study was employed from November 2021 to November 2023. Methods A total of 24 isolates underwent antimicrobial susceptibility testing using the disk diffusion method, an extended-spectrum beta-lactamase (ESBL) production test, and molecular gene detection. Results The study found that 95.8% of clinical isolates were classified as multidrug-resistant. All isolates were resistant to ampicillin (100%). A high percentage of isolates were resistant to cefazolin (91.7%), ceftriaxone (87.5%), cefotaxime (87.5%), cefepime (87.5%), ciprofloxacin (83.3%), and sulfamethoxazole-trimethoprim (83.3%). Of the 24 isolates, 87.5% harbored ESBL genes, while the frequencies for GES, NDM, SIM, and OXA-48 were 16.7%, 20.8%, 8.3%, and 41.7%, respectively. Notably, the OXA-23 and OXA-51 genes, which are typically associated with Acinetobacter baumannii, were detected in 16.7% and 20.8% of isolates, respectively. Moreover, the prevalence of virulence genes rmpA, acrAB, and tolC was 0%, 95.8%, and 87.5%, respectively. Conclusion This study demonstrated a high level of antibiotic resistance and a significant presence of virulence genes among K. pneumoniae isolates. Consequently, these findings represent a critical public health issue that requires heightened awareness among all stakeholders, including health workers.